SKETCH-DRAWINGS AND SKETCHES AS A METHOD OF NATURE RESEARCH - O.Yu. Shcherbakov (Academy of Cognitive and Natural Sciences, 2022)
In the article is examined the problem of didactic terms and receptions of forming systems approach during the prosecution of school-drawing in a section "Drawing of a human figure" as a development component of creative capabilities of students.